ChemInform Abstract: Synthesis of [Zn(II)BHPPDAH] as New Heterogeneous Catalyst Without Being Immobilized on Any Support and Applied for Mannich Reaction. Issue 4 (28th January 2014) - Khalifeh, Reza; Sharghi, Hashem; Rashidi, Zahra
Abstract The newly synthesized Zn complex is used as a catalyst for the three‐component coupling reaction of aldehydes, alkynes, and secondary amines.